BUZZ GROUP TECHNIQUE (BGT) IN TEACHING READING COMPREHENSION - ardayati ardayati; Vahdatul Nindiana (STKIP PGRI Lubuklinggau, 2018)
This research was conducted to answer a question of : “ Is it effective using Buzz Group Technique (BGT) in teaching Reading comprehension?” Therefore, this research aimed to find out whether or not it was effective using Buzz Group Technique (BGT) in teaching Reading. The pre – experimental was applied in this research. The population was all the eighth grade students of SMP Negeri H. Wukirsari which consisted of 120 students. The sample was taken through cluster random sampling. There were 26 students from VIII E class as sample. The data were analyzed through four technique; (1) individual score, (2) Conversion of individual score based on Minimum Mastery Criteria (MMC), (3) Normality testing, and 4) Matched t-test. The result of this study were (1) the average score in pre-test was 39.84, (2) the average score in the post-test was 75.23, and (3) the result matched t-test was 8.098, which higher than 1.708 t-table.The critical value of 95% with degree of freedom (df) = 25 (26-1) significant level was 0.05. Therefore, the null hypothesis (Ho) was rejected and alternative hypothesis (Ha) was accepted. Finally, it was efective to use Buzz Group Technique (BGT) in teaching reading comprehension.